Six-month incidence and persistence of oral HPV infection in HIV-negative and HIV-infected men who have sex with men. - Sofie H Mooij (Public Library of Science (PLoS), 2014)
Objectives Our aim was to assess incidence and persistence of oral HPV infection in HIV-negative and HIV-infected men who have sex with men (MSM). Methods MSM aged ≥18 years were included in Amsterdam (the Netherlands) in 2010-2011, and followed up 6 months later. Participants completed risk factor questionnaires. HPV DNA was analyzed in oral-rinse and gargle specimens using the SPF10-PCR DEIA/LiPA25 system (version 1). A subset of oral samples was subjected to SPF10 sequencing to identify additional HPV types. Multivariable logistic regression analyses using generalized estimating equations (GEE) were performed to assess determinants for oral high-risk HPV incidence and persistence. Results 689/795 participant MSM provided both baseline and 6-month data. Baseline prevalence of high-risk HPV was 9.4% in HIV-negative and 23.9% in HIV-infected MSM (P<0.001). 56/689 MSM acquired ≥1 high-risk HPV infection (6-month incidence 8.1%; 95%CI 6.2-10.4%); incidence was 4.1% in HIV-negative and 14.1% in HIV-infected MSM (P<0.001). HIV infection and recent use of cannabis were both independently associated with high-risk HPV incidence. Persistent high-risk HPV was observed in 48/130 (36.9%) infections. Conclusion Incidence of oral high-risk HPV infection in MSM is substantial, and is associated with HIV infection. Over a third of HPV infections persisted over a 6-month period.